The importance of social media in managing the image of the educational institutions - Waldemar Jędrzejczyk; Stanisław Brzeziński (Contemporary Economics, 2021)
The subject of the article relates to the use of social media in organizational activities aimed at creating a positive image of an organization. The image is an important element of the organization's strategy-it shapes its distinctiveness, distinguishes it from competitors, and determines how the organization is perceived in the environment. Image is created at the interconnection between the organization and its stakeholders. A significant role in the process of shaping the image is played by marketing communication, which is subjected to increased virtualization due to the progressing digital transformation. The attributes of social media predestine them to be used in the process of image creation. The main purpose of this article is to assess the importance of social media in the process of managing the image of educational institutions. The rules of the market economy apply not only to business organizations but also increasingly to other types of organizations, including educational institutions. Following the example of enterprises, educational institutions must also build a positive image of the organization. In the presented empirical research results, the research subject was narrowed down to one type of educational institution, namely secondary schools. The research has shown that all analyzed schools use social media and the school's website as tools to promote and build their image in the local community. Unfortunately, the effectiveness of using these tools is low.
Keywords: M10; M15; M31; M50; 330; Image of the organization; social media; educational institutions; Poland